Las TICs y el aprendizaje en el Área de Comunicación de Estudiantes de Sexto Grado en el I.E. Nicanor Rivera Cáceres de Barranco, 2021. - Marlene Julissa García Vilca (iQuatro Editores, 2022)
La investigación tuvo como objetivo identificar en qué medida se utilizan las TIC y el aprendizaje, en el área de comunicación, de los estudiantes de sexto grado en el I. E. Nicanor Rivera Cáceres, de Barranco (2021). El software CmapTools solo se empleó con el grupo experimental pero la evaluación de pretest y el postest se aplicó a ambos grupos. El nivel de investigación fue descriptivo correlacional; asimismo, se obtuvo la confiabilidad del instrumento de aprendizaje colaborativo mediante la prueba KR-20, que arrojó como resultado 0,857. Por tanto, se concluyó que el uso del software CmapTools mejora notablemente el aprendizaje colaborativo. Abstract The aim of this research was establishing the relationship between Information and Communication Technologies (ICT) and learning in the area of communication among sixth grade students from Nicanor Rivera Caceres Educational Institute (I.E. Nicanor Rivera Cáceres) de Barranco, Peru. To gather the information a quantitative approach methodology was applied, with a correlational scope and a non-experimental and cross-sectional design. The survey was used as a technique and the questionnaire as a research instrument. The population and sample consisted of 49 sixth grade students, from which the inferential result was that there existed a relationship between the ICT variable and learning with a Pearson value of 0.454 and a p-value of 0.002. It was concluded that when using ICTs continuously among students, learning is achieved much faster, more productively and more beneficial for them.